The 4S-AF Scheme (Stroke Risk; Symptoms; Severity of Burden; Substrate): A Novel Approach to In-Depth Characterization (Rather than Classification) of Atrial Fibrillation - Potpara, Tatjana S.; Lip, Gregory Y. H.; Blomstrom-Lundqvist, Carina; Boriani, Giuseppe; Van Gelder, Isabelle C.; Heidbuchel, Hein; Hindricks, Gerhard; Camm, Alan John (Thrombosis and haemostasis, 2021)
Abstract Atrial fibrillation (AF) is a complex condition requiring holistic management with multiple treatment decisions about optimal thromboprophylaxis, symptom control (and prevention of AF progression), and identification and management of concomitant cardiovascular risk factors and comorbidity. Sometimes the information needed for treatment decisions is incomplete, as available classifications of AF mostly address a single domain of AF (or patient)-related characteristics. The most widely used classification of AF based on AF episode duration and temporal patterns (that is, the classification to first-diagnosed, paroxysmal, persistent/long-standing persistent, and permanent AF) has contributed to a better understanding of AF prevention and treatment but its limitations and the need for a multidimensional AF classification have been recognized as more complex treatment options became available. We propose a paradigm shift from classification toward a structured characterization of AF, addressing specific domains having treatment and prognostic implications to become a standard in clinical practice, thus aiming to streamline the assessment of AF patients at all health care levels facilitating communication among physicians, treatment decision-making, and optimal risk evaluation and management of AF patients. Specifically, we propose the 4S-AF structured pathophysiology-based characterization (rather than classification) scheme that includes four AF- and patient-related domains—Stroke risk, Symptoms, Severity of AF burden, and Substrate severity—and provide a hypothetical model for the use of 4S-AF characterization scheme to aid treatment decision making concerning the management of patients with AF in clinical practice.